2022
DOI: 10.3389/fnhum.2022.928583
|View full text |Cite
|
Sign up to set email alerts
|

How shifting visual perspective during autobiographical memory retrieval influences emotion: A change in retrieval orientation

Abstract: Visual perspective during autobiographical memory (AM) retrieval influences how people remember the emotional aspects of memories. Prior research in emotion regulation has also shown that shifting from an own eyes to an observer-like perspective is an efficient way of regulating the affect elicited by emotional AMs. However, the impact of shifting visual perspective is also dependent on the nature of the emotion associated with the event. The current review synthesizes behavioral and functional neuroimaging fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 117 publications
0
14
0
Order By: Relevance
“…Instead, we found that shifts in observer perspective were particularly associated with reductions in the consistency of emotion/thought details, indicating that observer perspective might reflect an ability to change one’s internal experience of an event after it has occurred. Shifting to an observer perspective can impact the emotionality of memories (Küçüktaş & St. Jacques, 2022), perhaps allowing us to distance ourselves from the past so that we can remember events without reexperiencing every detail (Fernández, 2015; Libby & Eibach, 2011; McIsaac & Eich, 2004; Siedlecki, 2015). Indeed, observer perspectives are more likely to accompany recollection of events that elicit high degrees of self-awareness or distress (D’Argembeau & Van der Linden, 2008; Rice & Rubin, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we found that shifts in observer perspective were particularly associated with reductions in the consistency of emotion/thought details, indicating that observer perspective might reflect an ability to change one’s internal experience of an event after it has occurred. Shifting to an observer perspective can impact the emotionality of memories (Küçüktaş & St. Jacques, 2022), perhaps allowing us to distance ourselves from the past so that we can remember events without reexperiencing every detail (Fernández, 2015; Libby & Eibach, 2011; McIsaac & Eich, 2004; Siedlecki, 2015). Indeed, observer perspectives are more likely to accompany recollection of events that elicit high degrees of self-awareness or distress (D’Argembeau & Van der Linden, 2008; Rice & Rubin, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Visual perspective is a required feature of remembering (Rubin & Umanath, 2015), such that event memories do not simply involve isolated knowledge or facts, but the creation of a scene in the which the rememberer's viewpoint provides a central focus to the setting, objects, other people, and actions that occur. In this way, visual perspective can be considered a type of retrieval orientation, which biases how memories are reconstructed (Küçüktaş & St. Jacques, 2022;Robinson & Swanson, 1993). Consistent with this idea, both behavioral (Harris et al, 2015) and functional neuroimaging (Iriye & St. Jacques, 2020) evidence points to the role of early retrieval processes that distinguish own eyes and observer-like perspectives and impact how the contents of memories are elaborated upon.…”
Section: How Visual Perspective Reshapes Memoriesmentioning
confidence: 78%
“…Similarly, other studies have shown that shifting from an own eyes to an observer-like perspective reduces the vividness of subsequent memory recall, but when participants are asked to shift back to their original own eyes perspective they do not recover the loss visual information (Butler et al, 2016). Functional neuroimaging research has demonstrated that changes in subjective characteristics of memories as the result of shifting to an observer-like perspective are supported by neural recruitment in the precuneus (St. Jacques et al, 2017), suggesting that perspective influences behavior by altering the brain networks that support perceptual aspects of remembering (Küçüktaş & St. Jacques, 2022). Together these findings support the idea that shifting perspective can lead to plastic and potentially long-lasting changes in the phenomenology of memory, and that these changes are reflected by differences in the brain regions recruited during remembering.…”
Section: How Visual Perspective Reshapes Memoriesmentioning
confidence: 79%
See 1 more Smart Citation
“…Additionally, other research has demonstrated that adopting an observer-like perspective reduces elements that imbue memories with the sense of reexperience, such as the vividness of visual information (St Jacques, 2022), degree of emotional intensity (Küçüktaş & St Jacques, 2022), and the setting in which events occurred (Hebscher et al, 2018;Rubin, 2020).…”
Section: Statement Of Relevancementioning
confidence: 99%